Exploring the use of social media as a digital study guide - Shemberger, Melony; Wright, Leigh (Journal of Interdisciplinary Studies in Education, 2019)
The purpose of this case study was to understand how students could study for course examinations using social media. This study used two theoretical frameworks, Web 2.0 Technologies and connectivism, as the guiding concepts to explore how students in an introductory college course perceived the use of Twitter and Storify as test reviews and study guides. Forty-six university students in a journalism course were surveyed about their perceptions of these approaches. Results showed students believed the Twitter in-class review helped them to recall information more effectively. In addition, students used Storify as a study guide, and most said Storify helped to improve their test grades. Recommendations to modify this pedagogical approach and future research ideas are discussed.